ADVANCING COMMUNITY’S LITERACY CULTURE: AN ANALYSIS OF THE ROLE OF READ ALOUD COMMUNITY BANDUNG - Dina, Islami; Nurhayati, Sri (JURNAL DIMENSI, 2025)
This study analyzes the role of the Read Aloud Community Bandung in advancing community-based literacy culture through parent-led reading practices. Using a qualitative, phenomenological approach, data were collected through in-depth interviews with nine parents participants and one community founder along with direct observation and documents study. Thematic analysis revealed seven key domains. First, literacy is viewed as a form of cultural capital, yet constrained by structural barriers including cost, time, and societal perceptions. Second, participants’ initial reading aloud experiences were marked by emotional engagement and improved cognitive stimulation. Third, the practice of reading aloud was found to enhance vocabulary, comprehension, and school readiness. Fourth, significant challenges were identified, including digital distractions, parental isolation, and myths about book ownership. Fifth, the initiative fostered confidence, peer learning, and a renewed sense of purpose among participants. Sixth, while the organization thrives on volunteerism, it faces limitations in scalability and continuity. Lastly, the community proposed practical strategies for expansion, such as local coordinators and inclusive outreach. These findings suggest that the Read Aloud Community Bandung effectively repositions literacy as a relational, accessible, and community-driven practice, contributing valuable insights to the discourse on grassroots literacy development in under-resourced urban contexts.